Characteristics of pork emulsion gel manufactured with hot-boned pork and winter mushroom powder without phosphate. (March 2023) - Jeong, Hyun Gyung; Jo, Kyung; Lee, Seonmin; Yong, Hae In; Choi, Yun-Sang; Jung, Samooel
Abstract: This study investigated the physicochemical characteristics of pork emulsion gels manufactured from hot-boned (HB) pork and winter mushroom powder in the absence of phosphate. It was found that compared to cold-boned (CB) pork, HB pork had a higher pH and exhibited a higher myofibrillar protein solubility with a lower actomyosin content ( P < 0.05). Four types of pork gels were prepared, namely CB pork without phosphate, CB pork with phosphate (CBP), HB pork without phosphate, and HB pork with winter mushroom powder but without phosphate (HBW). The total exuded fluid was comparable for the CBP and HBW gels on all storage days. In addition, the HB and HBW gels had similar springiness and cohesiveness properties to the CBP gel ( P > 0.05). These results indicate that the quality of pork gels manufactured in the absence of phosphate can be improved by the use of HB pork and with the incorporation of winter mushroom powder. Highlights: HP pork had a higher solubility of MPs and lower actomyosin content than CB pork. The total exudated fluid (%) did not differ between the CBP gel and the HBW gel. The hardness values of the HB and HBW gels were lower than that of the CBP gel. The springiness and chewiness improved in the HB and HBW gels. The use of HB pork and winter mushroom powder improved the quality of pork gels.